2021
DOI: 10.3389/frsc.2021.713300
|View full text |Cite
|
Sign up to set email alerts
|

Are Cities Safer Than Before?

Abstract: Cities are built to lead better lives. However, irrational urban development has led in reverse, causing numerous problems. The increase in flood risk in urbanized areas is one of the significant problems. Despite extensive research, numerous engineering projects have been carried out to reduce the risk of flooding, the question “are we safer than before?” remains underexplored. The present work is a case study aimed at providing new evidence of the current state of flood disaster management. It analyzed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Historical records showed that 26 largescale flood disasters have occurred in the watershed of the Chikuma River from 1742 to 2020, and 11 of them occurred since 1980. 15 In 2019, the levee of the waterway at the Hoyasu location breached, and the inundation resulted in a 974,000,000 JPY loss in the Nagano City. 16 There is a hydrological gauging station (Kuiseke) 25.6 km upstream of the levee breach site, and another one (Tategahana) 5.5 m downstream of the breaching site.…”
Section: Methodsmentioning
confidence: 99%
“…Historical records showed that 26 largescale flood disasters have occurred in the watershed of the Chikuma River from 1742 to 2020, and 11 of them occurred since 1980. 15 In 2019, the levee of the waterway at the Hoyasu location breached, and the inundation resulted in a 974,000,000 JPY loss in the Nagano City. 16 There is a hydrological gauging station (Kuiseke) 25.6 km upstream of the levee breach site, and another one (Tategahana) 5.5 m downstream of the breaching site.…”
Section: Methodsmentioning
confidence: 99%